Arterial stiffness and risk factors of cardiovascular disease - A P Rebrov; N M Nikitina; N A Karoli; N A Magdeeva; I A Kharitonova; D A Kondakova; A P Rebrov; N M Nikitina; N A Karoli; N A Magdeeva; I A Kharitonova; D A Kondakova (Терапевтический архив, 2009)
Aim. To investigate arterial stiffness (AS) in healthy subjects and its correlation with standard cardiovascular risk factors (CRF). Material and methods. AS was estimated on Tensioclinic arteriograph (Tensiomed, Hungary) in 97 subjects (76 females and 21 males) having symptoms of neither atherosclerosis nor coronary heart disease (CHD). Detection of CRF was made by questionnaire survey. 10-year CHD risk and cardiovascular death risk (SCORE) were estimated. Results. With age, there was a rise of augmentation index (AI) (r = 0.76; p < 0.001) and pulse wave velocity (PWV) in the aorta (r = 0.61; p < 0.001), AI changes arose earlier than those of aortic PWV. Arterial hypertension is an independent factor of arterial stiffness deterioration. High blood cholesterol, AS, body mass index, smoking index directly correlate with AI and PWV in young subjects. CHD risk and SCORE rise with an AS increase (r = 0.30; p < 0.05 and r = 0.34; p < 0.05, respectively). Conclusion. Of CRF, most significant determinant of AS are arterial hypertension and age. AI is a more sensitive marker of AS in young subjects. Increased aortic PWV is more typical for persons over 50 years of age. The study of pulse wave characteristics with application of Tensioclinic arteriograph is a simple and significant method of detecting early changes in AS.